2021
DOI: 10.37313/1990-5378-2021-23-2-17-28
|View full text |Cite
|
Sign up to set email alerts
|

Method of Improving the Quality of Theoretical and Experimental Research at the Stage of Development Complex Technical System

Abstract: On the example of development a unique on-board gasification system for non-produced residues of liquid fuel in the tanks of the launch vehicle stage, the improvement of the quality of theoretical and experimental research is considered. Due to the uniqueness of the developed on-board gasification system, which begins functioning after the main liquid rocket engine (LRE) is turned off, there are no studies of the proposed method of gasification (evaporation) based on the supply of a carrier heat in the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Evaluation of the effectiveness of the proposed approach to improve the quality at the stage of scientific research showed that the reliability of the obtained information (calculated and experimental) increased by 10 -15% [5], the cost of resources for research decreased by 20-25%, the time for debugging the program of numerical simulation reduced by 15-20%, increased productivity was 22%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evaluation of the effectiveness of the proposed approach to improve the quality at the stage of scientific research showed that the reliability of the obtained information (calculated and experimental) increased by 10 -15% [5], the cost of resources for research decreased by 20-25%, the time for debugging the program of numerical simulation reduced by 15-20%, increased productivity was 22%.…”
Section: Discussionmentioning
confidence: 99%
“…where: w is the HC input rate, λ is the thermal conductivity, α is the heat transfer coefficient, ν is the kinematic viscosity, a is the thermal conductivity coefficient, 𝒍 is the characteristic size. Figure 2 below shows the scheme of the process of application of the proposed approach in order to improve the reliability of PM [5]. By introducing the proposed requirements and validation and verification criteria [8], which allow improving the quality of theoretical-experimental studies, the following results are achieved: -rejection of invalid measurements; -timely troubleshooting; -reduction of the resources spent on the experiment.…”
Section: Emimentioning
confidence: 99%
See 3 more Smart Citations